Industrial agroforestry – Status and developments in Tamil Nadu - Parthiban, K.T.; Fernandaz, C. Cinthia (Indian Journal of Agroforestry, 2020)
Agroforestry has been playing a critical role since time immemorial to satisfy the demands of domestic needs of wood and wood products. However, with the economic development coupled with the associated urbanization and industrialization, the demand for wood and wood products have increased rapidly, but there is no concomitant plantation development programme. Though the forests have supported the demands till the recent past, due to policy and legal restrictions, the supply of wood from natural forests have declined or almost stopped. Against this backdrop, Forest College and Research Institute of Tamil Nadu Agricultural University has conceived and implemented A Value Chain Model on Industrial Agroforestry in Tamil Nadu. This model has identified the constraints and problems in the entire Production to Consumption System (PCS) in agroforestry. These constraints have been resolved through technological, organizational and marketing interventions. The development of high yielding short rotation clones amenable for varied industrial utility, adoption of precision silvicultural technology, development of profitable and multifunctional agroforestry models, establishment of value addition technology, introduction of mechanization and assurance of price supportive system coupled with tree insurance have attracted farmers towards industry based tree husbandry. Accordingly pulp and paper; match, plywood, dendro power and timber industries have all been linked through the system in order to cater the needs of tree growing farmers. All these activities have established industrial agroforestry plantation to the tune of over 70000 ha in a span of 8 years and increased the overall productivity and profitability of the landuse system. This model has been institutionalized by developing a Consortium of Industrial Agroforestry (CIAF) which has taken a lead role in sustaining these activities towards establishment of successful agroforestry plantations to create self reliance in domestic and industrial raw material requirement besides catering the needs of climate change associated risks.